2012
DOI: 10.1155/2012/186138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low‐Frequency Alternative‐Current Magnetic Susceptibility in Ni80Fe20 Thin Films

Abstract: X-ray diffraction (XRD) results indicate that the NiFe thin films had a face-centered cubic (FCC) structure. Post-annealing treatment increased the crystallinity of NiFe films over those at room temperature (RT), suggesting that NiFe crystallization yields FCC (111) texturing. Post-annealing treatments increase crystallinity over that obtained at RT. This paper focuses on the maximum alternative-current magnetic susceptibility(χac)value of NiFe thin films with resonance frequency(fres)at low frequencies from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The results suggest that the maximum χ ac increased from 0.03 to the highest value of 0.27 as t f increased from 18 nm to 90 nm. These results could be explained by considering the nano-magneto crystalline anisotropy of the (110) nanocrystalline crystallization [35]. The maximum χ ac results were in line with previous XRD diffracted studies.…”
Section: Resultssupporting
confidence: 90%
“…The results suggest that the maximum χ ac increased from 0.03 to the highest value of 0.27 as t f increased from 18 nm to 90 nm. These results could be explained by considering the nano-magneto crystalline anisotropy of the (110) nanocrystalline crystallization [35]. The maximum χ ac results were in line with previous XRD diffracted studies.…”
Section: Resultssupporting
confidence: 90%
“…The results suggest that an excitation frequency of 10 to 30 Hz maximizes the χ ac of the magnetic exchange-coupled signal, and as the frequency increases above 30 Hz, the χ ac obtained from the signal declines, suggesting that the CoFeB/MgO/CoFeB MTJ is suited to use at low frequencies. The optimal maximum susceptibility, at frequencies in the range of 10 to 30 Hz, can be utilized in inductors and transformers [28,29]. …”
Section: Resultsmentioning
confidence: 99%
“…This result agrees with the data of Llavona et al [52], which show that, for potential values really similar to the two values we used in this work to perform the pulsed deposition, the NWs composition is quite homogeneous. 47-1405) [61,[65][66][67][68]. Chang et al [66] found that with the increase of Fe, the alloy changes from fcc phase to bcc.…”
Section: Morphological and Chemical Characterizationmentioning
confidence: 99%
“…In particular, the best alloys are those with other transition metals, such as NiPd [27,28], NiMo [29][30][31], NiZn [32,33], or, even more evidently, with the metals of the iron group, such as NiCo [34][35][36] and NiFe [37]. In addition to the excellent electrocatalytic property and high chemical stability in alkaline media, the latter are known for their mechanical and magnetic properties [38][39][40], making them excellent materials in the field of microelectromechanics.…”
Section: Introductionmentioning
confidence: 99%